Dramatic clinical response following dabrafenib and trametinib therapy in a heavily pretreated low grade serous ovarian carcinoma patient with a BRAF V600E mutation - Alberto A. Mendivil; Paul K. Tung; Randy Bohart; Karen Bechtol; Bram H. Goldstein (Elsevier, 2018)
Low grade serous ovarian cancer (LGSOC) is a slowly growing, relatively chemoresistant neoplasm that is associated with a more favorable prognosis, especially compared to the disease's high-grade serous counterpart. We recount a case involving a 47-year-old, heavily pretreated LGSOC patient who presented with an elevated CA-125 of 1047 U/mL during her recent course of pemetrexed therapy. Thereafter, she underwent molecular profiling, which revealed a BRAF V600E mutation; accordingly, the patient was administered dabrafenib and trametinib combination therapy, a regimen that resulted in a precipitous decline of her CA-125 to 35 U/mL following the 6th cycle. The patient's favorable response to BRAF and MEK 1/2 inhibitor therapy underscores the significance of molecular profile testing and the use of targeted therapy regardless of tissue origin, especially in cases for whom standard management is limited or ineffective. Keywords: Low grade serous ovarian cancer, BRAF mutation, Dabrafenib, Trametinib